Integrated Learning Management Science in Junior High School 2 Kartasura Academic Year 2015-2016 - Arif Munandar (Lembaga Penelitian dan Pendidikan Mandala, 2017)
This study aimed to describe the learning management Integrated Science in public junior high school 2 Kartasura. This research is classified as qualitative research with phenomenological approach. Informants were included in this study is an educator (teacher) Integrated Science, homeroom teacher, and principal. The focus of the study are: instructional planning, implementation of learning, and assessment of learning Integrated Science in public junior high school 2 Kartasura. Data were gathered through structured interviews, observation, and documentation, as well as the data analysis technique used is the model Milles and Huberman. The results showed that the learning management Integrated Sciences in public junior high school 2 Kartasura not run optimally. Planning science teaching science educators use lesson plans and syllabi are not in accordance with the lesson plan provided by the relevant agencies. Implementation of Integrated Science learning is not in the mix and this is not in accordance with the Decree of the Minister of Republic of Indonesia number 22 of 2006 on the Content Standards. Integrated science teaching assessment result-oriented, the evaluation is done by two methods, namely: Evaluation of short-term and long-term. But educators natural Sciences does not undertake remedial program for students who did not complete. As a result, if learners are not completed, Integrated Science educators directly menuntaskannya accordance with minimum completeness criteria (MCC) subjects and was not in accordance with regulation minister of national education of the Republic Indonesia Processing Standards number 41 in 2007.